Characterization and outcomes of 414 patients with primary SS who developed haematological malignancies. (6th April 2022) - Hernández-Molina, Gabriela; Kostov, Belchin; Brito-Zerón, Pilar; Vissink, Arjan; Mandl, Thomas; Hinrichs, Anneline C; Quartuccio, Luca; Baldini, Chiara; Seror, Raphaele; Szántó, Antonia; Isenberg, David; Gerli, Roberto; et al.
Abstract: Objective: To characterize 414 patients with primary SS who developed haematological malignancies and to analyse how the main SS- and lymphoma-related features can modify the presentation patterns and outcomes. Methods: By January 2021, the Big Data Sjögren Project Consortium database included 11 966 patients fulfilling the 2002/2016 classification criteria. Haematological malignancies diagnosed according to the World Health Organization (WHO) classification were retrospectively identified. Results: There were 414 patients (355 women, mean age 57 years) with haematological malignancies (in 43, malignancy preceded at least one year the SS diagnosis). A total of 376 (91%) patients had mature B-cell malignancy, nearly half had extranodal marginal zone lymphoma (MZL) of mucosa-associated lymphoid tissue (MALT lymphoma) ( n  = 197), followed by diffuse large B-cell lymphoma (DLBCL) ( n  = 67), nodal MZL lymphoma ( n  = 29), chronic lymphocytic leukemia/small lymphocytic lymphoma (CLL/SLL) ( n  = 19) and follicular lymphoma (FL) ( n  = 17). Rates of complete response, relapses and death were 80%, 34% and 13%, respectively, with a 5-year survival rate of 86.5% after a mean follow-up of 8 years. There were significant differences in age at diagnosis (younger in MALT, older in CLL/SLL), predominant clinical presentation (glandular enlargement in MALT lymphoma, peripheral lymphadenopathy in nodal MZL and FL, constitutional symptoms in DLBCL, incidental diagnosis in CLL/SLL), therapeutic response (higher in MALT lymphoma, lower in DLBCL) and survival (better in MALT, nodal MZL and FL, worse in DLBCL). Conclusion: In the largest reported study of haematological malignancies complicating primary SS, we confirm the overwhelming predominance of B-cell lymphomas, especially MALT, with the salivary glands being the primary site of involvement. This highly-specific histopathological scenario is linked with the overall good prognosis with a 5-year survival rate of nearly 90%.